Betulinic Acid Exerts Anti-inflammatory Activity in Human Periodontal Ligament Cells Stimulated with Lipopolysaccharide and/or High Glucose - Hu, Ping; Zhu, Chunxia (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Diabetic patients have weakened periodontal ligaments and an increased risk of periodontitis due to uncontrolled glycemia. Betulinic acid (BA), a hypoglycemic drug, has anti-inflammatory activities. Objectives: The current study aimed to explore the protective effect of BA on the inflammation in human periodontal ligament cells (PDLCs) stimulated with lipopolysaccharide (LPS) and/or high glucose (HG) status and its mechanisms of action. Methods: Human PDLCs were exposed to LPS and/or HG, with or without BA intervention. The production of nitrite oxide (NO) and prostaglandin E2 (PGE2) were quantified by Griess reaction and enzyme-linked immunosorbent assay, respectively. Immunoblotting analyses were employed to detect the expression of inducible nitric oxide synthase (iNOS) and the cyclooxygenase-2 (COX- 2), as well as the activation of mitogen-activated protein kinases (MAPKs) and nuclear factor kappa- B (NF-ΚB) in human PDLCs. Results: The increased production of iNOS/NO and COX-2/PGE2 and increased phosphorylated levels of IΚBα, JNK, and p38 can be detected in human PDLCs with LPS and/or HG situations, while increased phosphorylated ERK can be seen in cells under only LPS condition. Furthermore, the non-toxic concentration of BA (10 μM) prevented NF-ΚB and MAPKs activation and partly but significantly reversed the induction of COX-2/ PGE2 and iNOS/NO in human PDLCs with LPS and/or HG loaded. Conclusion: BA was proved for the first time to protect human PDLCs from the LPS-induced and/or HG-induced inflammation, which works through the mechanism involving the action of MAPKs and NF-ΚB. signaling pathways. Thus, BA could be used to alleviate diabetic complications of periodontitis.
Keywords: nuclear factor kappa-B